Konstruksi Sosial Peran Domestik Perempuan dalam Unggahan Instagram Produk Rumah Tangga di Indonesia - Rr. Siti Kurnia Widiastuti (Yayasan Azhar Amanaa Yogyakarta, 2026)
Digital media serves as both a tool for marketing communication and a social environment where ideas about gender are formed and continually reinforced. While gender representation in television advertising or digital campaigns has been the primary focus in previous studies, there is little research on how household product brands construct women's domestic roles on Instagram. This study tackles that gap by looking at how gender is represented through the viewpoints of Social Construction Theory and Gender Performativity. The study employs a qualitative interpretive method to examine official Instagram posts from household product brands in Indonesia, such as detergents, dishwashing liquids, cooking seasonings, children's milk, and baby diapers. The analysis examines visual images, the individuals depicted, everyday household tasks, and the underlying gender ideas present in online content. The study shows that women are still mostly shown as the main people doing household cleaning, cooking meals, and taking care of children, while men are more often depicted as helpers, people who benefit from these tasks, or only sometimes involved in housework. Despite this, there are several posts that show men taking part in cooking, taking care of children, and doing household tasks, which suggests a growing effort to achieve more equal gender roles. The results indicate that Instagram posts serve as both commercial channels and a means for Indonesians to perpetuate and reestablish their gender roles in the digital age. The study adds value to the field of gender and media research by building on earlier work about digital advertising, specifically through an analysis that compares different categories of Instagram content related to household products. The results also offer useful guidance for advertisers and digital content creators to create more balanced and gender-inclusive portrayals in their digital marketing messaging